Uncertainty analysis in the management of gas metering systems - Papadopoulos, Christos E. (Cranfield University, 2000)
In the natural gas market, open access along with gas brokering and marketing has resulted in multiple gas contracts through one physical measuring point Accurate metering of natural gas has become more important than ever as deregulation subjects pipeline companies to competition. A more competitive market is driving the need for real-time accurate electronic flow measurement. Modern electronic natural gas metering systems (ENGMS) introduced additional, though necessary, complexity in the estimation and verification of the reported results. Additionally, it becomes more and more important to be able to verify these results. The application of Monte Carlo simulation as a combined energy flow measurement uncertainty estimation method seems to offer specific advantages over the more complex, traditional uncertainty estimation methods while at the same time fully conforms with the method of the ISO/GUM, (the authoritative document for uncertainty evaluation). Since, Monte Carlo simulation relies on randomness, it seems to capture more naturally and to have a more direct connection with the underlying physics of measurement uncertainty. Typical comparisons of estimated uncertainties using the Monte Carlo method and the conventional method (RSS) have been carried out. In general Monte Carlo gave slightly higher estimated uncertainties. This is due to the fact that the simplified conventional methods inevitably neglect correlations between the variables. A methodology for gas management decision making based on Monte Carlo uncertainty estimation is proposed. According to this, uncertainty analysis could be incorporated in any management decision making process regarding metering systems and importantly through all stages, from selection and design of a metering system up to real operation. In addition to the Monte Carlo simulation, work regarding possible improvements to orifice flow measurement quality is considered.